Successful Therapy of Alopecia Universalis Using a Combination of Systemic Methotrexate and Corticosteroids and Topical 5% Minoxidil - Ruchiatan K; Avriyanti E; Hindritiani R; Puspitosari D; Suwarsa O; Gunawan H (Dove Medical Press, 2022)
Kartika Ruchiatan, Erda Avriyanti, Reti Hindritiani, Diah Puspitosari, Oki Suwarsa, Hendra Gunawan Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran - Dr. Hasan Sadikin General Hospital, Bandung, West Java, IndonesiaCorrespondence: Kartika RuchiatanDepartment of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran - Dr. Hasan Sadikin General Hospital, Pasteur 38, Bandung, West Java, 40161, Indonesia, Tel +62222032426 ext. 3449; +62811247932, Email kartika.ruchiatan@unpad.ac.idAbstract: Alopecia areata (AA) is an autoimmune disease-specific to specific organs mediated by T lymphocytes with hair follicles as targets. Severe AA could be in the form of alopecia universalis (AU). AU therapy is relatively difficult and challenging with varying outcomes. Herein, we reported a case of AU in a 19-year-old man with alopecia in the hairy scalp area, eyebrows, eyelashes, moustache, beard, and axillary hair since 2.5 years ago. The patient's severity of alopecia tool (SALT) score was 100%. The patient was given a combination therapy of 15 mg methotrexate per week and 16 mg methylprednisolone per day orally and topical treatment with minoxidil 5%. Observations after nine months of treatment showed an improvement in the decrease in SALT scores to 41%. However, striae were found after 3rd month of therapy. Systemic combination therapy of methotrexate and low-dose corticosteroids and topical minoxidil 5% in this patient gave responsive results. Performed the hematological examination, liver function levels, blood glucose levels, and cortisol during long-term use of methotrexate and corticosteroids are necessary. The combination of systemic methotrexate and corticosteroids, and topical minoxidil showed promising results in AU. Nevertheless, long-term observation is still needed to monitor the side effects of therapy.Keywords: alopecia areata, alopecia universalis, corticosteroid, methotrexate, minoxidil